2021
DOI: 10.3390/ijerph18115625
|View full text |Cite
|
Sign up to set email alerts
|

Association between Crystalline Silica Dust Exposure and Silicosis Development in Artificial Stone Workers

Abstract: Occupational exposure to respirable crystalline silica (SiO2) is one of the most common and serious risks because of the health consequences for the workers involved. Silicosis is a progressive, irreversible, and incurable fibrotic lung disease caused by the inhalation of respirable crystalline silica dust. A cross-sectional epidemiological study was carried out to assess the occupational risk factors that may contribute to the onset of silicosis in workers carrying out work activities with the inhalation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…Proper ventilation, good work habits, a hygienic workplace, safe and healthy occupational training, and regular occupational health examinations are key factors in controlling respirable dust exposure and reducing occupational lung disease [ 32 , 33 , 34 , 35 ]. Studies have found that the use of ventilated cabs can reduce exposure to dust from engineering operations by approximately 6 times, and the use of wet operations can significantly reduce the dust exposure of workers by 3 times [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proper ventilation, good work habits, a hygienic workplace, safe and healthy occupational training, and regular occupational health examinations are key factors in controlling respirable dust exposure and reducing occupational lung disease [ 32 , 33 , 34 , 35 ]. Studies have found that the use of ventilated cabs can reduce exposure to dust from engineering operations by approximately 6 times, and the use of wet operations can significantly reduce the dust exposure of workers by 3 times [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silica (also known as silicon dioxide, SiO 2 ) is a widely abundant mineral compound of the Earth's crust, and can be found in rocks, concrete, artificial stone, glass, and other industrial materials [11,12]. Silica occurs in non-crystalline (amorphous) and crystalline forms.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los criterios de riesgo de enfermedad pulmonar fibrótica de origen laboral, encontramos que la mayoría estuvo expuesto 10 o más años al material de riesgo, lo que es un argumento robusto a favor de la sospecha de origen laboral (21) . Con relación a los EPIs, la respuesta de que la mayoría no dispusiera de mascarillas en los primeros años, se corresponde con el conocimiento que se tiene de aquella época (22,23) . En cuanto a los materiales a los que estuvieron expuestos aquellos trabajadores, también es consecuencia de las ocupaciones características de nuestra región, como la exposición mixta a sílice y amianto en moldeadores/macheros de industrias de fundición de acero (24) .…”
Section: Discussionunclassified